The Labor Market Effects of Reducing the Number of Illegal Immigrants - Andri Chassamboulli; Giovanni Peri (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2015)
A controversial issue in the US is how to reduce the number of illegal immigrants and what effect this would have on the US economy. To answer this question we set up a two-country model with search in labor markets and featuring legal and illegal immigrants among the low skilled. We calibrate it to the US and Mexican economies during the period 2000-2010. As immigrants, especially illegal ones, have a worse outside option than natives their wages are lower. Hence their presence reduces the labor cost of employers who, as a consequence, create more jobs per unemployed when there are more immigrants. Because of such effect our model shows that increasing deportation rates and tightening border control weakens the low-skilled labor markets, increasing unemployment of native low skilled. Legalization, instead decreases the unemployment rate of low-skilled natives and it increases income per native.
Keywords: F22; J61; J64; 330; job creation; search costs; illegal immigrants; border controls; deportations; legalization; unemployment; wages